2011
DOI: 10.1021/es104190k
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides on Household Surfaces May Influence Dietary Intake of Children

Abstract: The physical and chemical environment influences children's exposures to pesticides in and around the home. Children's activities, which increase their potential for exposure especially during eating, have been captured in the Children's Dietary Intake Model (CDIM). In addition to the chemical exposure associated with the food itself, this model incorporates excess dietary exposures due to handling of food during consumption. To stochastically evaluate CDIM, distributions of measured, and in some cases estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In addition, the food may have higher pesticide residues depending upon how it is stored in these homes that may have increased residential pesticide contamination due to proximity to agricultural fields or through direct contact with contaminant surfaces [57]. Although few pesticides were detected in the duplicate diet measurements, these measurements do account for potential contamination during food storage and preparation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the food may have higher pesticide residues depending upon how it is stored in these homes that may have increased residential pesticide contamination due to proximity to agricultural fields or through direct contact with contaminant surfaces [57]. Although few pesticides were detected in the duplicate diet measurements, these measurements do account for potential contamination during food storage and preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Stapleton et al demonstrated that reported hand-washing behaviour is associated with reduced PBDE concentrations in children's hand-wipe samples, which could lead to decreased exposure to PDBEs via non-dietary ingestion or trans-dermal absorption given that they have previously demonstrated that hand-wipe concentrations of PBDEs are correlated with PBDE body burden (118). Young children may also ingest toxicants through excess dietary exposure that occurs when toxicants transfer from their hands or other surfaces in the home to foods that they then consume (119). No studies have assessed -through questionnaires -whether exposure of children to EDCs may be modified by variables that could reduce excess dietary exposure like washing hands prior to eating.…”
Section: Behaviour: a Major Knowledge Gapmentioning
confidence: 99%
“…In children, excess dietary exposure, i.e., ingestion of toxicants that have transferred to foods from contaminated hands or surfaces, may contribute substantially to total exposure (119). Additionally, as discussed earlier, exposure through the diet to plasticisers may be modified by how plastic food contact materials are used, what foods they come into contact with and how the food is prepared.…”
Section: Limiting Error Through Attention To Questionnaire Designmentioning
confidence: 99%
“…Although analytical methods for measuring 88 Figure 1 Major exposure pathways of young children to insecticides: mechanisms for increased exposure risk relative to adults Increased exposure via inhalation is attributable to higher concentrations of insecticides found in the infant breathing zone, compared to the adult breathing zone, and the relatively greater intake of air by infants (Fenske, Black et al 1990). Frequent hand-to-mouth behaviour predisposes infants to greater non-dietary insecticide exposure (Melnyk, Byron et al 2011), and the relatively greater consumption of food by infants compared to adults also contributes to greater dietary intake (Roberts and Karr 2012). Increased contact with contaminants found on the floor in dust, as well as the greater relative surface area of infants, predisposes to greater levels of dermal absorption (Makri, Goveia et al 2004).…”
mentioning
confidence: 99%